PENGARUH PUPUK ORGANIK DAN ANORGANIK TERHADAP KANDUNGAN LOGAM BERAT DALAM TANAH DAN JARINGAN TANAMAN SELADA - Erita Hayati (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2010)
The objective of this research was to study content of heavy metal (Pb) in soil and lettuce tissue caused by organic and inorganic fertilizers application. This research applied a factorial completely randomized design (CRD) with 3 replicates. The first factor was organic fertilizer, consisting of 4 levels and the second factor was inorganic fertilizers, consisting of 2 levels. Variables observed were fresh weight, and content of heavy metal in soil and tissue. Results showed that application of organic and inorganic fertilizers could reduce level of lead Pb) in soil and plant tissue. The highest Pb concentration was in the treatment without organic fertilizer and the lowest Pb concentration was in the organic fertilizer of 45 tons per ha, which was not significantly different from the organic fertilizer of 30 tons per ha. The highest plant fresh weight was obtained in dosage of organic fertilizer 15 tons/ha in the second planting. The best combination for plant fresh weight was an organic fertilizer of 15 tons/ha and an inorganic fertilizer of 1000 kg/ha.